Recent Patents on Shut off Nozzle for Injection Molding Machine - Wang, Jiankang; Li, Zhanyong; Liu, Xiangyang (Recent Patents on Mechanical Engineering, 2015)
As a main component of injection molding machine, nozzle is used to prevent polymer melt from leaking during plasticizing and provide an access injecting polymer melt into the mold cavity during injecting process. The straight-through nozzles and shut off nozzles with hydraulic or pneumatic are adopted in the traditional injection molding machine. The paper reviews various patents on nozzles with new structures and optimized design in recent years. A spring-sliding valve type nozzle is introduced to solve melt leaking, nozzle blocking, and melt thermal decomposition. Moreover, this new type of shut off nozzle is more compacted and low-cost.
Keywords: sliding valve